Heightened fear in response to a safety cue and extinguished fear cue in a rat model of maternal immune activation - Sangha, Susan; Greba, Quentin; Robinson, Paul D.; Ballendine, Stephanie A.; Howland, John G. (Frontiers in Behavioral Neuroscience, 2014)
Maternal immune activation during pregnancy is an environmental risk factor for psychiatric illnesses such as schizophrenia and autism in the offspring. Hence, changes in an array of behaviors, including behavioral flexibility, consistent with altered functioning of cortico-limbic circuits have been reported in rodent models of maternal immune activation. Surprisingly, previous studies have not examined the effect of maternal immune activation on the extinction of fear conditioning which depends on cortico-limbic circuits. Thus, we tested the effects of treating pregnant Long Evans rats with the viral mimetic polyI:C (gestational day 15; 4 mg/kg; i.v.) on fear conditioning and extinction in the male offspring using two different tasks. In the first experiment, we observed no effect of polyI:C treatment on the acquisition or extinction of a classically conditioned fear memory in a non-discriminative auditory cue paradigm. However, polyI:C-treated offspring did increase contextual freezing during the recall of fear extinction in this non-discriminative paradigm. The second experiment utilized a recently developed task to explicitly test the ability of rats to discriminate among cues signifying fear, reward, and safety; a task that requires behavioral flexibility. To our surprise, polyI:C-treated rats acquired the task in a manner similar to saline-treated rats. However, upon subsequent extinction training, they showed significantly faster extinction of the freezing response to the fear cue. In contrast, during the extinction recall test, polyI:C-treated offspring showed enhanced freezing behavior before and after presentation of the fear cue, suggesting an impairment in their ability to regulate fear behavior. These behavioral results are integrated into the literature suggesting impairments in cortico-limbic brain function in the offspring of rats treated with polyI:C during pregnancy.